PENGEMBANGAN PRODUK DIVERSIFIKASI OLAHAN IKAN BULAN – BULAN (Megalops cyprinoides) PADA MITRA BINAAN POKLAHSAR INDRI SEJAHTERA KOTA TARAKAN - Arlina Hidayati; Mutmainnah; Istyqamah Muslimin; Nurmaida; Imra; Stephanie Bija; Christine Dyta Nugraeni; Nurasmi; Tri Paus Hutapea; Reni Tri Cahyani; Sumarlin; Novi Luthfiyana; Ira Maya Abdiani; Mohammad Fadnan Akhmadi (Jurnal Abdi Insani, 2026)
The “Indri Sejahtera” Fisheries Group is a beginner group that produces fishery products, but it has encountered several problems in both production and marketing. The variety of processed fish products is still quite limited, so contemporary innovations are needed to compete in the market. One such innovative product is rambutan fish. Rambutan fish is a processed fish product made by grinding fish meat, shaping it into balls, coating it with dumpling skin strips, and deep-frying it until crispy. When fried, the outer layer stands up, resembling the hair-like strands of a rambutan fruit. This community service activity was carried out using a mentoring approach. This mentoring method was implemented through several stages: the delivery of educational materials, the training on how to make rambutan fish, and the monitoring and evaluation of the activity. The training on processing mackerel into a value-added product—rambutan fish—was successfully conducted at the Indri Sejahtera Poklahsar Tarakan. The material was presented by the speaker in a clear and logical accompanied by a hands-on demonstration of how to prepare “ikan bulan-bulan” as “ikan rambutan,” covering everything from ingredient preparation and dough-making to shaping and frying. Based on the questionnaire results, 93% of participants expressed satisfaction with the training activity, with knowledge increasing from 20% to 100% and participants’ skills improving from 10% before the training to 100%. The training was able to enhance partners’ understanding regarding the utilization of moonfish into diversified processed products. This activity provided insights into scientific knowledge and the application of appropriate technology in producing competitive products.